Abdominoperineal Approach to Uterovaginal Anastomosis in Cervical Dysgenesis: A Case Report and Review of Literature - Ajay Halder; Shweta Patel; Pankhuri Dubey (The Surgery Journal, 2022)
Genital outflow tract obstruction due to cervical agenesis is an uncommon Mullerian duct anomaly, increasingly being treated with conservative surgery by creation of an outflow tract by drilling or coring into the cervical remnant or by uterovaginal anastomosis. A 19-year-old woman with cervical dysgenesis in the present case underwent a successful uterovaginal anastomosis to relieve the obstructive menstrual symptoms and preserve the future reproductive function. The neouterovaginal canal was created over a mold of Foley's catheter by anastomosis anterior surface of the uterine corpus to the vaginal vault, bypassing the dysgenetic cervix and using the fibrous band of cervix as support. Normal cyclical menses were restored. Steps of the procedure are detailed in this case report.